Pilot study of food-specific go/no-go training for overweight individuals: brain imaging data suggest inhibition shapes food evaluation. Issue 1 (17th December 2021) - Yang, Yingkai; Morys, Filip; Wu, Qian; Li, Jiwen; Chen, Hong
Abstract: Food-specific go/no-go training might reduce overeating and facilitate weight loss. In this pilot study, we examined whether a food-specific go/no-go training over five weeks, as compared to a non-food-specific training, could produce changes in behavioral and neural responses to food images and body weight. Here, we used a sample of 51 overweight participants divided into training and control groups whose brain activity and food evaluation were measured before and after the training. Compared with the control group, in the training group we found significant reductions in high-calorie food evaluation. We also found lower activations in inhibitory control- and reward-related brain regions in response to high-calorie food images. Further, activation change of the mid-insula in response to the high-calorie food images was positively associated with change in the evaluation of those images. However, we found no evidence for a significant effect of food-specific go/no-go training on body weight change. Our findings highlight that food-specific go/no-go training in overweight individuals can reduce high-calorie food evaluation, but also neural activations in inhibitory control- and reward- related brain regions.